TGF-β-Induced Endothelial to Mesenchymal Transition Is Determined by a Balance Between SNAIL and ID Factors - Ma, Jin; van der Zon, Gerard; Gonçalves, Manuel A. F. V.; van Dinther, Maarten; Thorikay, Midory; Sanchez-Duffhues, Gonzalo; ten Dijke, Peter (Frontiers in Cell and Developmental Biology, 2021)
EEndothelial-to-mesenchymal transition (EndMT) plays an important role in embryonic development and disease progression. Yet, how different members of the transforming growth factor-β (TGF-β) family regulate EndMT is not well understood. In the current study, we report that TGF-β2, but not bone morphogenetic protein (BMP)9, triggers EndMT in murine endothelial MS-1 and 2H11 cells. TGF-β2 strongly upregulates the transcription factor SNAIL, and the depletion of Snail is sufficient to abrogate TGF-β2-triggered mesenchymal-like cell morphology acquisition and EndMT-related molecular changes. Although SLUG is not regulated by TGF-β2, knocking out Slug also partly inhibits TGF-β2-induced EndMT in 2H11 cells. Interestingly, in addition to SNAIL and SLUG, BMP9 stimulates inhibitor of DNA binding (Id) proteins. The suppression of Id1, Id2 or Id3 expression facilitated BMP9 in inducing EndMT and, in contrast, ectopic expression of ID1, ID2 or ID3 abrogated TGF-β2-mediated EndMT. Altogether, our results show that SNAIL is critical and indispensable for TGF-β2-mediated EndMT. Although SLUG is also involved in the EndMT process, it plays less of a crucial role in it. In contrast, ID proteins are essential for maintaining endothelial traits and repressing the function of SNAIL and SLUG during the EndMT process. These data suggest that the control over endothelial versus mesenchymal cell states is determined, at least in part, by a balance between the expression of SNAIL/SLUG and ID proteins.